Structural Performance of Ferrocement Beams containing Plastic Waste Fibers and Longitudinal Holes Filled with Lightweight Concrete - Jamal Alobeadi, Abdulrahman; Al-Hadithi, Abdulkader Ismail; Aldosary, Muhannad Haqqi (Iraqi Journal of Civil Engineering, 2025)
Ferrocement is a type of concrete made of mortar with different wire meshes. It has wide and varied applications in addition to its strength and durability. This research aims to combine ferrocement and sustainability, as over time, the consumption of plastics, especially plastic bottles, has increased and has serious negative effects if buried, burned, or chemically analyzed. Therefore, this research aims to benefit from this plastic waste and introduce it into the construction field by using plastic waste fibers in the concrete mixture instead of cement at a rate of 0.5% and 1% by volume. This research studied the mechanical properties of nine samples of ferrocement beams with dimensions of 1200 × 200 × 150 mm3. A longitudinal hole with a diameter of 50 mm was drilled in different places of the beams and filled with lightweight concrete to facilitate the use of the hole in service passes when drilled, with a study of the initial cracking loads and the resulting deflection in addition to the failure modes and the deflection resulting from the maximum load. The results showed an improvement in load resistance with an improvement in deflection at the maximum load, In addition to an increase in the improvement of Toughness and Stiffness of ferrocement beams.